INFLUENCE OF SUBTOXIC DOSES OF COMPLEX ORGANIC MIXTURES, BASED ON GLYCOLS, ON OKSIDATION AND ANTIOKSIDATION SYSTEMS OF WHITE RATS ORGANISM - Sirenko, E. V.; Zykov, V. I.; Kycherenko, E. A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The state of the oxygenation and antioxygenation systems of white rats organism, which got the subtoxic doses of complex organic mixtures, based on the glycols, were investigated in subacute experiment. It was demonstrated, that the action of the organic substances causes the accumulation the diene conjugates (DC), malondialdegyde (МDА) in the blood serum, decreases the activity of the membrainspecific lipid enzymes, glucose-6-phosphatedtgydrogenes, glutationperoxyde, SH-groups of the blood, increases the vitamine C contents in the adrenal glands and the glutation in the blood of rats. It was shown the ability of the investigated substances to stimulate the oksidationsystem, that can cause to the exhaustion of antioxydation system and damage the cellular membrane by the active forms of the oxygen.